Influence of incident energy on the properties of arc rated para-aramid fabric. Issue 21 (November 2021) - Li, Xia; Sun, Qilong; Wang, Shuo; Tang, Hong
To study the protection mechanism of para-aramid fabrics under an electric arc, the structural composition, surface morphology, and thermal properties of an untreated para-aramid fabric and that treated with different incident energy arcs were compared. The intensity of the N-H peak of the para-aramid cellulose amide decreased with increasing exposed arc energy. Moreover, intensities of the C=O peak of the amide bond type I carbonyl and the C-H deformation vibration absorption peak originating from the benzene ring gradually weakened. In contrast, the carbon content of the fabric increased. In the arc deflagration process, the fiber broke and then carbonized and embrittled. With an arc energy of 30.9 cal/cm 2, the carbonization degree of the front surface of the fabric increased and was highest at the float line. The initial combustion temperature remained unchanged, and the mass residual quantity gradually increased with increasing arc energy exposed to the fabric. The above results suggest that para-aramid fabric can protect the end user in an arc by carbonization, offering effective assistance in the research and development of personal protective equipment for arc flashes.